Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Pasien di Puskesmas Barukku Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Anti, Ardi; Sellang, Kamaruddin; Lukman, Lukman; Syarifuddin, Haeruddin (Universitas Gajah Putih, 2025)
This study aims to determine the influence of public service quality on patient satisfaction at the Barukku Public Health Center, located in Pitu Riase District, Sidenreng Rappang Regency. The population of this study consisted of 42 patients who had received services in the past two months. The research involved two variables: variable X (public service quality) and variable Y (patient satisfaction). A simple random sampling technique was employed, involving 42 respondents. This research utilized a descriptive quantitative approach. Data were collected through observation, questionnaires, and literature review. The data analysis techniques included validity and reliability tests using IBM SPSS Statistics 21.0. The results showed that public service quality has a significant influence on patient satisfaction at Barukku Public Health Center. Based on the recapitulation results, 60% of respondents rated the public service quality as